1991
DOI: 10.1007/bf00028737
|View full text |Cite
|
Sign up to set email alerts
|

Amber codon suppression: the in vivo and in vitro analysis of two C-hordein genes from barley

Abstract: A 1420 bp genomic fragment (lambda-hor1-17) encompassing a Hor-1 gene encoding a C-hordein polypeptide is presented. The deduced amino acid sequence is 261 residues long. It comprises a 20 amino acid signal peptide, unique NH2- and COOH-terminal regions and a coding region comprised of pentapeptide (PQQPY) and octapeptide (PQQPFPQQ) repeat motifs. The 431 bp of 5' non-coding region contains a 'TATA box' at -105, a 'CACA box' (-181 to -201) and a -300 prolamin element. In the 3' non-coding region there are two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 68 publications
0
27
0
2
Order By: Relevance
“…The EB of the promoter of a Hor-2 gene is made of two cis-motifs, PB and GLM, that are well conserved in the promoters of prolamin genes of the Pooideae grasses, such are those encoding B-and C-hordeins in barley (22,36,37), ␣/␤ gliadins, and LMW-glutenins in wheat (38,39) and -secalins in rye (40). Our results show that BLZ2 binds in vitro in a sequence-specific manner to the GLM within the EB of a Hor-2 gene promoter and that mutations altering the sequence of the GLM disrupt the interaction.…”
Section: Do Blz2 and Blz1 Interact In Bombarded Barleymentioning
confidence: 99%
“…The EB of the promoter of a Hor-2 gene is made of two cis-motifs, PB and GLM, that are well conserved in the promoters of prolamin genes of the Pooideae grasses, such are those encoding B-and C-hordeins in barley (22,36,37), ␣/␤ gliadins, and LMW-glutenins in wheat (38,39) and -secalins in rye (40). Our results show that BLZ2 binds in vitro in a sequence-specific manner to the GLM within the EB of a Hor-2 gene promoter and that mutations altering the sequence of the GLM disrupt the interaction.…”
Section: Do Blz2 and Blz1 Interact In Bombarded Barleymentioning
confidence: 99%
“…Evidence for readthrough was obtained both in vitro by translation in the wheatgerm system and in vivo by transient expression of reporter gene fusions in barley endosperm tissue after particle gun bombardment. Although the authors demonstrated that the promoter of this particular gene is even more active than that of a control wild-type Chordein gene, the absence of both full-length or truncated proteins after in vitro translation of barley endosperm mRNA showed that they represent a minor component of the storage proteins in barley endosperm (Entwistle et al, 1991). The sequencing of genes belonging to a maize c~-zein subfamily 4 (SF4) gene cluster provided evidence that four of the genes designated type 2 (T2) contained one or two early in-frame stop codons (Liu & Rubenstein, 1993).…”
Section: Stop Codon Suppressionmentioning
confidence: 98%
“…Stop codon suppression has also been implicated in the expression of plant genes such as the synthesis of storage proteins in barley (C-hordeins; Entwistle et al, 1991) and maize (c~-zeins; Liu & Rubenstein, 1993). The C-hordein ORF in the genomic clone 2-horl-14 is interrupted by an amber stop codon within the coding sequence for the octapeptide repeats.…”
Section: Stop Codon Suppressionmentioning
confidence: 99%
“…Cloning and sequencing of structural genes for B-, C-, and γ-hordein polypeptides have corroborated that the Hor 1, Hor 2, and Hor F loci each consist of a family of closely linked structural genes for these proteins, with each gene having its own promoter (7,10,18,24,62,63,70). Some of these genes contain stop codons, but transient transformation experiments revealed that expression of such a gene in the endosperm can take place by amber codon suppression (19).…”
Section: Prefacementioning
confidence: 99%